2001
DOI: 10.1080/00288233.2001.9513473
|View full text |Cite
|
Sign up to set email alerts
|

Serum progesterone levels using radioimmunoassay during oestrous cycle of indigenous Damascus does

Abstract: An experiment was conducted on Damascus does to characterise the oestrous cycle and activity of the corpus luteum and to determine normal progesterone patterns during different phases of the oestrous cycle using radioimmunoassay. Fifteen 2-5-year-old indigenous cycling Damascus does were used during the normal breeding season for two consecutive oestrous cycles. Average length of the oestrous cycles was 21.2 ± 1.5 days (range: 19-26 days), consisting of 2.9 + 0.8 days (2-5 days) where progesterone level was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
12
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
(23 reference statements)
9
12
1
Order By: Relevance
“…The P4 concentrations remained at basal levels throughout the estrus as observed by others (Zarkawi and Soukouti 2001;Khadiga et al 2005). In Damascus goats, the P4 level during luteal phase ranged from 2.6 to 5.4 ng mL −1 (Khadiga et al 2005), which is comparable to the levels in Markhoz goats.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The P4 concentrations remained at basal levels throughout the estrus as observed by others (Zarkawi and Soukouti 2001;Khadiga et al 2005). In Damascus goats, the P4 level during luteal phase ranged from 2.6 to 5.4 ng mL −1 (Khadiga et al 2005), which is comparable to the levels in Markhoz goats.…”
Section: Discussionsupporting
confidence: 72%
“…Assessment of progesterone (P4) and estradiol-17β (E2) levels during different physiological stages in animals is considered one of the most important parameters to determine their fertility status (Zarkawi and Soukouti 2001). Little information is available regarding changes in P4 and E2 levels during different reproductive stages in Markhoz goats compared to that in other farm animals (Riesenberg et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…previously. 20 In addition, the P 4 concentrations in a 1999 study 6 observed during the early luteal phase agree with the data reported in the current study. Moreover, the highest concentrations of P 4 were associated with the presence of corpora lutea.…”
Section: Discussionsupporting
confidence: 89%
“…The P 4 concentrations in cyclic goats decline and reach minimal concentrations during estrus, after which they gradually increase and reach maximal concentrations in the luteal phase. 6,10,20 In the current study, there was a close temporal relationship between the significant decrease in plasma P 4 concentrations measured by the TR-FAT and the manifestations of behavioral estrus. Mean plasma P 4 concentrations in this period were typical for the periestrous period.…”
Section: Discussionsupporting
confidence: 71%
“…Thus the earliest diagnosis of pregnancy in Malabari goats in this study with the serum progesterone estimation was done on day 17 th post insemination. The progesterone level was low in non-pregnant goats from day 16 to 21 as reported by Zarkawi and Soukouti (2001), Medan et al (2004) and Titi et al (2008). Padilla-Rivas et al (2005) reported the detection of amniotic vesicle by day 19.5 ± 0.3 post insemination in Boer goats as the first indication of pregnancy.…”
Section: Resultsmentioning
confidence: 75%